The Influence of Tea Party Learning Strategies Assisted by Poster Media on Learning Results in Class VII Islamic Religious and Character Education Learning at SMP Negeri 30 Padang - Muhamad Azmy; Martin Kustati; Nana Sepriyanti (al-Afkar, Journal For Islamic Studies, 2025)
The low learning outcomes for Islamic Religious Education and Character Class VII at SMP Negeri 30 Padang in 2021/2022 are the background to this research. Most students have not reached the KKM that the school has set at 80. One way that can be used to overcome low learning outcomes is to use tea party learning strategies assisted by poster media in learning Islamic Religious Education and Character. The aim of writing this thesis is (1) To find out the implementation of tea party learning strategies assisted by poster media in learning Islamic Religious Education and Character Class VII at SMP Negeri 30 Padang. (2) To find out the results of learning in class VII Islamic Religious and Character Education at SMP Negeri 30 Padang. (3) To find out the influence of Tea Party learning strategies assisted by poster media on learning outcomes in Islamic Religious Education and Character Class VII learning at SMP Negeri 30 Padang.